Classification of Rapists in Massachusetts, 1980-1990 - Prentky, R. A. ([Verlag nicht ermittelbar], 1995)
The purpose of this study was to apply the latest version of a typological system for rapists (MTC:R3) developed at the Massachusetts Treatment Center for Sexually Dangerous Persons (MTC) to a large sample of offenders currently or previously incarcerated at MTC and to examine the system's reliability and concurrent and predictive validity. Data are available from two of the project's components. In the first component, 201 rapists who were committed to MTC between 1958 and 1981 were classified. This sample was used to revise the previous classification system (R2), upon which the development of the current system rests. Of these 201 men, 94 were in residence at the time of the study and 107 had been released. The second component classified a sample of 54 rapists who were committed after 1981. This sample was not used to develop the criteria for the typology. As an overview, this project had two missions: (1) to subtype about 250 rapists using MTC:R3 criteria, and (2) to utilize an archivally-derived database to examine the concurrent and predictive validity of the system. In addition to the subtype assignments, the primary source of data was the detailed institutional files that were used to code a 1,500-variable questionnaire.